Evaluación de un paquete de tratamientos para el control de plagas en almacenamiento del grano seco de maíz suave y duro para consumo.” Saquisilí - Cotopaxi 2015 - Corrales Sánchez, Edwin Alexander (2015)
Corn is an annual grass of fast growth and high production, it is adapted to different climate and soil conditions, it is the third most important crop in the world, and therefore it has the necessity of make this research since in Ecuador in the Sierra, Costa and Amazon Region according to the FAO report mentions that 25% cereals in post-harvest is lost, so aim of the research is "Evaluate a package of treatments for controlling pest in dry, soft and hard corn storage " , This research was performed to provide alternatives to the problem in an easy. It was used inductive-deductive scientific method, experimental techniques of observation and data collection in the field….